Influence of temperature drop on the pressure rise in the fan circuit of the gas turbine engine turbo-fan attachment - Roman Maiboroda (Авіаційно-космічна техніка та технологія, 2023)
The subject of this study is the working process in a turbofan attachment of a gas turbine engine. The object of study is the fan part of the impeller of a turbofan attachment. The aim of this study was to evaluate the effect of temperature difference in a two-tier impeller on the degree of pressure increase in the fan part of a two-tier impeller of a turbofan attachment of a three-circuit engine. To achieve this goal, the following tasks were solved: to simulate the flow in a turbofan attachment; to calculate the dependence of the degree of pressure increase in the fan part of the impeller of the turbofan attachment on the Mach number for the operating mode at altitudes of 0 km, 9 km and 11 km; to evaluate the temperature difference in the two-tier impeller of the turbofan attachment. The study was carried out by the method of numerical experiment. Results: The dependence of the degree of pressure increase of the fan circuit of the turbofan attachment on the Mach number at the inlet is obtained, taking into account the effect of hot gases of the turbine circuit of the turbofan attachment. It is shown that the flow of hot gases affects the degree of pressure increase in the fan circuit. The presence of the turbine part of the two-tier impeller leads to a slight deterioration in the characteristics of the fan part. The degree of pressure increase is reduced by 0.2 ... 4.8 %. The greatest influence is manifested in the operating mode H = 11 km. Visualization of the flow velocity field in the fan part of the turbofan unit showed that during the operation of the turbine circuit, the nature of the leakage in the fan part changes by approximately 50% of the blade height. An increase in temperature contributes to the intensification of the energy of the boundary layer around the lower part of the blade of the fan circuit, which has a positive effect on the reduction of zero velocity zones during the flow. Scientific novelty and practical significance: new data were obtained on the effect of temperature difference in a two-tier impeller on the degree of pressure increase in the fan part of a two-tier impeller of a turbofan attachment of a three-circuit engine. The results obtained can be used to optimize the turbofan attachment of a gas turbine engine.